The Effect of the Modernization of the Tax Administration System and Tax Understanding Level on the Individual Taxpayer Compliance at the South Lampung Dispenda Office - Dessy Andamisari; Heru Sudinta; Wuwuh Andayani; Santi Dwi Agustin (Jurnal Pajak Vokasi (JUPASI), 2022)
This study was aimed to determine the effect of the Tax Administration System and Tax Understanding Level on Individual Taxpayer Compliance at the South Lampung Dispenda Office. This research was quantitative research with a sample of 100 respondents. The data collection was by distributing questionnaires having been tested for their validity and reliability, while the data analysis was carried out using analysis of determination. The results of the study indicated that there was a simultaneous and significant effect between the Tax Administration System and Tax Understanding on the Compliance of Individual Taxpayers. This can be seen based on the F test and the value of Sig. The obtained value was 0.00 where < from 0.00 and the calculated f value was 48,876 > 3.09. This means that the independent variables, namely the Tax Administration System (X1) and Tax Understanding (X2), had a simultaneous effect on the dependent variable, namely Tax Compliance (Y). In the results of the t-test, it is known that the Tax Administration System (X1) variable had a Sig value of 0.000 <0.05 and a t-count of 0.8005> from a t-table of 1.988, then the data was declared influential. This means that the Tax Administration System variable (X2) affected the Tax Compliance variable. In the Tax Understanding variable (X2), the Sig value was 0.000 <0.05 and t count was 30.248 > t table 1.988, then the data could also be said influential. In conclusion, the Tax Understanding variable affected the Tax Compliance variable.